Design of a 2-DOF Control and Disturbance Estimator for a Magnetic Levitation System - A. Pati (Engineering, Technology & Applied Science Research, 2017)
This work proposes a systematic two-degree freedom control scheme to improve the reference input tracking and load disturbance rejection for an unstable magnetic levitation system. The proposed control strategy is a two-step design process. Firstly, a proportional derivative controller is introduced purposely to get the desired set-point response of the magnetic levitation system and then, an integral square error (ISE) performance specification is used for designing a set-point tracking controller. Secondly, a disturbance estimator is designed using the desired closed loop complimentary sensitivity function for the rejection of load disturbances. This leads to the decoupling of the nominal set-point response from the load disturbance response similar to an open loop control manner. Thus, it is convenient to optimize both controllers simultaneously as well as separately. The effectiveness of the proposed control strategy is validated through simulation.